The Analysis Of Taxpayer Compliance Through The Tax Review Implementation On Restaurant’s Tax - Ayi Srie Yuniawati; Shalsa Bila Farodis; Shofia Annisa Ratnasari (LPPM Universitas Sebelas April, 2022)
Restaurant Tax is one of Regional Tax type which is a source of regional income. As a Taxpayer, especially a Restaurant Tax, is obliged to pay taxes properly. The implementation of taxes, Bumdes Nanjung is still assisted by the village treasurer. Furthermore, in 2019-2021 tax payments, there are a number of fines. Therefore, it is necessary to do a Tax Review on the implementation of taxes that has been done. The purpose is to find out the tax compliance of the Bumdes Nanjung as a Taxpayer. This research was conducted through a qualitative approach with a case study method. The data obtained through observation, interviews, and documentation. The results of this study indicate that the implementation of taxes has not complied formally/administratively, but has complied and qualify with the provisions of material taxes. In addition, the implementation of taxes is still assisted by the village treasurer. Then the Bumdes Nanjung cannot be said and given the title of Obedient Taxpayer. It is hoped that Bumdes Nanjung can start obliged to pay tax by its own.